Into great silence [videorecording (DVD)] = Le grand silence = Die grosse Stille - Gröning, Philip, 1959- (Zeitgeist Films, 2007)
The Grande Chartreuse, considered one of the world's most ascetic monasteries is based in the French Alps. In 1984, German filmmaker Philip Gröning wrote to the Carthusian order for permission to make a documentary about them. They said they would get back with him. Sixteen years later, they were ready. Gröning, sans crew or artificial lighting, lived in the monks' quarters for six months - filming their daily prayers, tasks, rituals, and rare outdoor excursions.